An Expected Utility Function for the Insurance Buying Gambler - Eden, Benjamin (Review of Economic Studies, 1979)
Journal Article An Expected Utility Function for the Insurance Buying Gambler Get access Benjamin Eden Benjamin Eden Hebrew University of Jerusalem and Falk Institute for Economic Research Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 4, October 1979, Pages 741–742, https://doi.org/10.2307/2297040 Published: 01 October 1979 Article history Received: 01 December 1977 Accepted: 01 November 1978 Published: 01 October 1979